Soil characteristics and their relation to the development of tomato collar rot caused by Sclerotium rolfsii - and S.K. SUGHA, D.K. BANYAL, V. MANKOTIA (Indian Phytopathology, 2008)
In tomato, collar rot (Sclerotium roltsii) is one of the major threats in Himachal Pradesh with an incidence of 10-45 per cent. The present study elucidated the role of different soil parameters viz., texture, pH, moisture, nutrients (available nitrogen, phosphorous, potassium and organic carbon) and population dynamics of S. roltsii in the development of collar rot of tomato. Lighter soils were more favourable to the disease than the heavy textured soils. The maximum disease incidence was obtained at a pH 6.5. Low moisture favoured the disease development as compared to high moisture. The phosphorous and potassium had negative correlation, whereas nitrogen, soil pH, per cent organic carbon and pathogen population showed positive correlation. Nitrogen enhanced the disease whereas phosphorous and potassium decreased it.